A new species of Syndicus (s. str.) Motschulsky (Coleoptera, Staphylinidae, Scydmaeninae) from East China - Yin, Zi-Wei; Song, Xiao-Bin; Li, Li-Zhen (Zootaxa, 2014)
Syndicus (s. str.) jaloszynskii Yin and Song, new species is described from Fujian and Zhejiang, East China. All material was collected in rotten woods. The habitus of both sexes, aedeagus, and spermatheca are illustrated. The new species can be readily separated from all known congeners by the strikingly large body size, the structure of aedeagal endophallus, and the form of spermatheca. This is the first species of the nominotypical subgenus of Syndicus known to occur in China.